Counseling with Self-Management Techniques to Improve Learning Motivations - Riska Pratiwi; Yeni Karneli (Jurnal Neo Konseling, 2021)
The Covid-19 virus has an impact on the world of education, the impact of students is not ready and the most feared is the long-term effects. Another result is the loss of students' learning motivation. Learning motivation is a very important part of learning. Learning motivation is an intrinsic and extrinsic motivation or will that causes a person to do learning activities.This case study aims to help students improve learning motivation through individual counseling self-management techniques.This research uses descriptive methods through action research. The target audience in the case study with the title of improving learning motivation through individual counseling self-management techniques is 1 junior high school student located in Medan.Data collection techniques are observation and document study. The results obtained in the form of improved student learning motivation through individual counseling self management techniques.